INDONESIA NATIONALISMâ€™S CHALLENGE IN THE GLOBALIZATION ERA - Supardan, Dadang (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
We are still reminding that the long-term multidimensional crisis, the peak moment was in 1997-2000, was the worst experience in term of politic, economy, and law crisis after the Indonesia independence.The crisis may refer to a state-nation in turbulence (chaos) which many observers called as â€œA Country in Despairâ€, a country that is not only experiencing a disaster but also drowned in a deep despair. Indonesiaâ€™s multidimensional crisis had opened all the â€œmasksâ€, to its most hidden parts.This multidimensional crisis- in despair, emotionally, and sinically- had showed Indonesia as